Automatic Storage and Retrieval System (AS/RS) Design for Manufacturing System - KOÇ, Yusuf Ziya (International Journal of Computational and Experimental Science and Engineering, 2023)
In this article, the Automatic Storage and Retrieval System (AS/RS) desing used in automatic production systems and the AS/RS simulation technique were studied in this design. Part 1, which was created by simulating with computer code, was composed of two types of cells according to the dimensions of the space. Thanks to the prepared simulation, it offers the performance of AGVs, robots and collection-deposit stations. The simulation created has tested how long the warehouse can withstand periods of recession and depression. The simulation was run in two modes as single command mode and dual command mode. According to the obtained data, it has been obtained that the binary mode gives better performance compared to the single instruction. At the same time, this study; He proved that when the input speed is greater than the output speed, the binary instruction allows more items to be translated in a given time frame compared to a single instruction.